Identification of the Actual Shoreline Impact on Pond With ArcGIS Basemap Images In Muncar Sub-District, Banyuwangi Regency - Restu Ade Yanti; A Sediyo Adi Nugraha; Lutfiatul Jannah; Lilis Nuraini (Media Komunikasi FPIPS, 2022)
The regulatory law no. 32 of article 14 of 1990 is regulated at least 100 meters calculated from the highest tidal point towards the continent. Pond use must consider the distance from the shoreline to avoid losses. This research aims to discover the coastline influence on the sustainability of the ponds in the Muncar Sub-district. The methodology used in this study was digitized on the screen using the ArcGIS base map. The existence of a coastline in digitization for determining an area occurs abrasion or accretion. Then the pond is digitized to discover its existence, then computes the length of the shoreline. The results obtained the existence of the coastline that there are ponds along 15,907.87 m and no pond shoreline 8,173.02 m. In comparison, the number of working ponds can reach 247 plots. Among the five villages that have ponds, three have complied with the regulations. The Kumendung Village is 1432 meters, Sumbersewu Village is 336 meters, Kedungwringin Village is 857 meters eligible, and the other two villages are ineligible Tembokrejo Village along 5 meters and Wringinputih Village 7.3 meters. Ponds that do not comply with regulations are exposed to an abrasion hazard. Therefore, there need to be countermeasures such as backfilling or mangrove planting. Based on these findings, observations should be made to discover the truth of the shoreline existence against ponds that are at risk of abrasion.